Analisis Pengetahuan Konseptual, Prosedural, dan Metakognitif Siswa Melalui Pembelajaran Integrasi Flipped Classroom dan PBL - H Bintang; E Darnah; Ngia Masta; Rinaldi Rinaldi; T Guswantoro; M Sianturi (Faculty of Science and Education, UIN Walisongo Semarang, 2020)
Student-centered learning (SCL) is a learning approach that not only encourages to how student constructs their conceptual knowledge, but also to achieve the involvement of their knowledge in daily activity, in forms procedural and metacognitive knowledge. Flipped classroom learning models marked by reversed learning activities syntax between class and home, which promoted student to active self-learning, before turn into face to face class meeting. Problem Based Learning (PBL) model provides students to apply their knowledge to formulate strategy and solution in facing their problem. Flipped classroom or PBL, both are student-centered learning models that triggers student to self-constructed knowledge actively and student’s curiosity to solve their problem. This paper attempts to analyze the influence of integration flipped classroom and PBL on conceptual, procedural, and metacognitive knowledge on Linear Motion subject. This research is a quasi experimental model with post-test only control design. The population in this study were all students of class X MIPA SMA Negeri 37 Jakarta in the 2019-2020 school year. The sample in this study were students of class X MIPA 1 as the experimental class and class X MIPA 2 as the control class. The sample was taken using cluster sampling technique. The results obtained showed that the percentage of conceptual, procedural and metacognitive knowledge of the experimental class was 88.9%; 77.8%; and 88.9% which is higher than the control class with the respective percentage 66.7%; 55.8%; and 75%. The integration of the flipped classroom and PBL models can be applied to materials other than Linear Motion to improve conceptual, procedural, and metacognitive knowledge.